Sentiment Trading and Hedge Fund Returns - CHEN, YONG; HAN, BING; PAN, JING (Journal of Finance, 2021)
ABSTRACT In the presence of sentiment fluctuations, arbitrageurs may engage in different strategies leading to dispersed sentiment exposures. We find that hedge funds in the top decile ranked by sentiment beta outperform those in the bottom decile by 0.59% per month on a risk‐adjusted basis, with the spread being larger among skilled funds. We also find that about 10% of hedge funds have sentiment timing skill that positively correlates with fund sentiment beta and contributes to fund performance. Our findings show that skilled hedge funds can earn high returns by predicting and exploiting sentiment changes rather than betting against mispricing.